2014
DOI: 10.1021/nn503803b
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Photoluminescence Spectroscopy of Carbon Nanotubes with Localized Exciton States

Abstract: We report distinctive nonlinear behavior of photoluminescence (PL) intensities from localized exciton states embedded in single-walled carbon nanotubes (SWNTs) at room temperature. We found that PL from the local states exhibits strong nonlinear behavior with increasing continuous-wave excitation power density, whereas free exciton PL shows only weak sublinear behavior. The strong nonlinear behavior was observed regardless of the origin of the local states and found to be nearly independent of the local state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 73 publications
4
56
1
Order By: Relevance
“…4 , additional localized states were embedded in carbon nanotubes by atomic oxygen 32 or sp 3 -defect doping 34 that reduce the band gap and exciton energy locally. Oxygen- and the sp 3 -defect-doped carbon nanotubes were prepared according to procedures originally developed by Ghosh et al 32 and Piao et al 34 , respectively, with different chemical and experimental parameter selections 33 48 . In brief, the isolated nanotube dispersion was combined with a small amount of D 2 O containing dissolved ozone and left under the illumination of a desk lamp (ca.…”
Section: Methodsmentioning
confidence: 99%
“…4 , additional localized states were embedded in carbon nanotubes by atomic oxygen 32 or sp 3 -defect doping 34 that reduce the band gap and exciton energy locally. Oxygen- and the sp 3 -defect-doped carbon nanotubes were prepared according to procedures originally developed by Ghosh et al 32 and Piao et al 34 , respectively, with different chemical and experimental parameter selections 33 48 . In brief, the isolated nanotube dispersion was combined with a small amount of D 2 O containing dissolved ozone and left under the illumination of a desk lamp (ca.…”
Section: Methodsmentioning
confidence: 99%
“…[61] The long lifetime of the trapped excitons means that even moderate excitation densities lead to a saturation of the defect sites. Thus, the E 11 /E 11 * intensity ratio becomes highly pump power-dependent, [53,62] which makes the comparison of defect densities in experimental studies with different excitation sources (lamp, pulsed or continuous wave laser) very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers have concluded that the local electronic states generated from the defects are nearly independent of the origin. 15 Meanwhile, recent findings revealed that different functional groups on diazonium adducts could generate E 11 − peaks on (6,5) SWCNTs at a range of 1110 to 1148 nm. 12 For oxygen-based defects, Ghosh et al deduced the product of their ozone-functionalized SWCNTs to be ethers perpendicular to nanotube axis (ether-perpendicular) rather than epoxides.…”
Section: Introductionmentioning
confidence: 99%